ANALISIS PENERJEMAHAN FRASE: STUDI KASUS PADA PENERJEMAHAN FRASE BAHASA JEPANG KE BAHASA INDONESIA OLEH MAHASISWA STBA YAPARI-ABA BANDUNG - Asteria Permata Martawijaya; Yayat Hidayat (Jurnal Sora : Pernik Studi Bahasa Asing, 2018)
In this study, researchers analyzed the translated phrases from Japanese into Indonesian done by the sixth semester students of STBA Yapari-ABA Bandung. This research uses descriptive method by describing and interpreting what is in the field, to see conditions, ongoing processes or developing trends. The analysis results concluded that the translation’s tendency of noun-noun phrases, adjective-noun phrases and phrase verbs done by the sixth semester students of STBA Yapari-ABA Bandung is relative based on the words and sentences. The unacceptability tendency of the translation results is caused by the lack of understanding of language, both on the source language and the target language. In terms of phrase structure, the students tend to shift the compulsory and automatic form in the translation.